Understanding the role of metabolic syndrome in prostate cancer risk: A UK Biobank prospective cohort study - Shing Fung Lee; Maja Nikšić; Miguel Angel Luque-Fernandez (Scientific Reports)
Abstract Predictive value of metabolic syndrome for prostate cancer risk is not clear. We aimed to assess the association between metabolic syndrome and its components with prostate cancer incidence. The primary outcome was prostate cancer incidence, i.e., incidence rate ratios and adjusted cumulative incidence curves derived from flexible parametric survival models. Adjusted cumulative incidence curves were derived using a flexible survival parametrical modeling framework. We analysed UK Biobank data including 242,349 adult males, recruited during 2006–2010 and followed up until 2021, during which 6,467 (2.7%) participants were diagnosed with prostate cancer. Our findings indicate that metabolic syndrome, as a whole, was not associated with prostate cancer risk (incidence rate ratios, 1.07; 95% confidence interval, 0.94–1.22). However, specific components such as hypertension and obesity increased the risk (incidence rate ratios, 1.22; 95% confidence interval, 1.03–1.44 and incidence rate ratios, 1.24; 95% confidence interval, 1.05–1.46, respectively). Other components, such as prediabetes/diabetes and low cholesterol, were associated with a reduced risk (incidence rate ratios, 0.80; 95% confidence interval, 0.67–0.94 and incidence rate ratios, 0.82; 95% confidence interval, 0.69–0.97, respectively), while hyperlipidaemia showed no significant effect (incidence rate ratios, 1.07; 95% confidence interval, 0.93–1.24). Further research is needed to understand the underlying mechanisms behind these relationships. Prostate cancer prevention strategies might benefit from targeting modifiable risk factors, particularly hypertension and obesity.